Government innovation subsidy, executives’ academic capital and innovation quality: Evidence from pharmaceutical companies in China - Xia, Yuntian; Fan, Min; Zuo, Xu; Hao, Wenjing; Jia, Yiwen (Frontiers in Psychology, 2023)
The government uses innovation subsidies as a key incentive strategy to encourage companies to innovate more technically. This study creates an innovation quality index for pharmaceutical corporations using categorizing data from patent applications submitted by pharmaceutical companies. Using data from 180 listed Chinese pharmaceutical enterprises from 2010 to 2020, this research presents a panel regression model to examine the moderating impact of executives' academic capital on the effect of government innovation subsidy on innovation quality. How well innovations are subsidized is also affected by the heterogeneity of property rights. The effect of innovation subsidies is stronger and more positive for non-SOEs. This article indicates that CEOs with academic credentials and executives with professional links to the pharmaceutical business have a range of moderate impacts. The research provides fresh ideas for improving the standard of corporate innovation and the innovation subsidy program.